The impact of interval vs. continuous training on exercise capacity and endothelial function in post-myocardial patients: a randomised control trial. (25th November 2020) - Novakovic, M; Kosuta, D; Trsan, J; Krevel, B; Tasic, J; Vizintin Cuderman, T; Rajkovic, U; Bozic Mijovski, M; Fras, Z; Jug, B
Abstract: Introduction: High-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) are two most common and well established exercise modalities for cardiac rehabilitation in patients after myocardial infarction. Yet, data on their effects on cardiovascular parameters beyond exercise capacity (e.g. endothelial function) are scarce. Methods: Patients referred to cardiac rehabilitation (CR) after myocardial infarction were randomised to HIIT or MICT. HIIT consisted of 7 cycles of 1.5 min of 80–90% VO2peak and 3 min of 65–70% VO2peak intensity; MICT consisted of 32 min of 75% VO2peak intensity. We ultrasonographically appraised flow-mediated dilation (FMD) – a marker of endothelial function – before (resting), immediately after and one hour after (a) the first and (b) the last exercise training session, in order to appraise the specific effects of HIIT vs. MICT on acute and long-term vascular response to training. Cardiopulmonary exercise testing was performed in all patients. We compared the effects of training modalities with ANCOVA using baseline values as covariates, and examined the improvement after CR in each intervention group with paired-samples t-test. Results: Eighty-six patients were included (55±10 years of age, 19% females), 43 in each group. There were no differences between HIIT and MICT groups in baseline characteristics. VO2peak improved in both groups (HIIT: 22.8 to 24.9 ml/kg/min, p=0.016 and MICT: 21.9 to 24.5 ml/kg/min, p<0.001), with no significant between-group differences (p=0.571). Also, resting FMD improved after both HIIT and MICT (4.6 to 6.7%, p=0.016, and 4.7 to 8.0%, p=0.001, respectively), with no significant between-group differences (p=0.177). Acute vascular response to training, however, improved with HIIT (FMD one hour after the last training session: 4.1 to 7.1%, p=0.022), but not MICT (5.9 to 6.4%, p=0.584). Conclusion: Both HIIT and MICT significantly and comparably improve exercise capacity and resting FMD in patients after myocardial infarction. In addition, however, HIIT is associated with improved vascular response during recovery period after exercise. Funding Acknowledgement: Type of funding source: None